COVID-19 vaccination up-take in three districts of Nepal. Issue 1 (31st December 2023) - Pokhrel, Tara Nath; Karki, Kshitij; Tinkari, Bhim Singh; Upreti, Shyam Raj; Khatiwada, Shikha Upadhyaya; Amatya, Rakchya; Zervos, John; Kaljee, Linda; Zenlea, Kate; Prentiss, Tyler; Maki, Gina; Shallal, Anita; et al.
ABSTRACT: Vaccine hesitancy during the COVID-19 pandemic continues to be an issue in terms of global efforts to decrease transmission rates. Despite high demand for the vaccines in Nepal, the country still contends with challenges related to vaccine accessibility, equitable vaccine distribution, and vaccine hesitancy. Study objectives were to identify: 1) up-take and intention for use of COVID-19 vaccines, 2) factors associated with vaccine up-take, and 3) trusted communication strategies about COVID-19 and the vaccines. A quantitative survey was implemented in August and September 2021 through an initiative at the Nepali Ministry of Health and Population Department of Health Services, Family Welfare Division. Data were collected from 865 respondents in three provinces (Bagmati, Lumbini, and Province 1). Ordinal multivariate logistic regression was utilized to determine relationships between vaccination status and associated factors. Overall, 62% (537) respondents were fully vaccinated and 18% (159) were partially vaccinated. Those respondents with higher education ( p < .001) and higher household income ( p < .001) were more likely vaccinated. There were also significant differences in vaccine up-take across the three provinces ( p < .001). Respondents who were vaccinated were significantly more likely to perceive vaccines as efficacious in terms of preventing COVID-19 ( p = .004) and preventing serious outcomes ( p = .010). Among both vaccinated and unvaccinated individuals, there was a high level of trust in information about COVID-19 vaccines provided through local health-care workers [e.g. nurses and physicians]. These results are consistent with other findings within the South Asia region. Targeted advocacy and outreach efforts are needed to support ongoing COVID-19 vaccination campaigns throughout Nepal.